Method for producing laminated sheet
The laminated sheet with a specific surface layer structure and anchor coating application using a gravure roll addresses the issue of floating aluminum vapor deposition films in cold containers, ensuring improved adhesion and durability.
Patent Information
- Application Number
- JP2023177570
- Authority / Receiving Office
- JP · JP
- Patent Type
- Applications
- Current Assignee / Owner
- Filing Date
- 2023-10-13
- Publication Date
- 2025-04-24
- Estimated Expiration
- 2043-10-13
AI Technical Summary
Existing laminated sheets used in cold containers often experience partial peeling of the aluminum vapor deposition film from the LDPE layer, leading to floating issues.
A laminated sheet with a surface layer structure where a layer of low density polyethylene (LDPE) is laminated on a layer of linear short chain molecular polyethylene (LLDPE), and an aluminum deposition layer is applied with an anchor coating (AC) agent using a gravure roll, ensuring a dry coating amount of 0.118 g/m².
The proposed solution effectively prevents the aluminum deposition film from floating by ensuring adequate adhesion between the aluminum film and the LDPE layer, thereby enhancing the durability and performance of the laminated sheet in cold container applications.
Smart Images

Figure 2025067518000001_ABST
Abstract
Description
[Technical field]
[0001] The present invention relates to a laminate sheet having a surface layer in which an aluminum vapor-deposited film coated with an anchor coat (AC) agent is laminated on a layer containing low-density polyethylene (LDPE), and to a cool storage container using the same. [Background technology]
[0002] 2. Description of the Related Art A laminated sheet used in cold storage containers such as cold storage covers and cold storage boxes has a surface layer made of an aluminum vapor-deposited film (see, for example, Patent Document 1).
[0003] A known surface layer has a layer structure in which a layer containing low-density polyethylene (LDPE) is laminated on a layer containing linear short-chain polyethylene (LLDPE), and an aluminum vapor-deposited film is further laminated on the layer containing LDPE, i.e., on the outermost surface.
[0004] It is also known that in order to improve adhesion between the LDPE-containing layer and the aluminum vapor-deposited film in a surface layer having such a configuration, a coating layer made of an anchor coat (AC) agent is formed on the LDPE-containing layer, and the aluminum vapor-deposited film is laminated via this coating layer. [Prior art documents] [Patent documents]
[0005] [Patent Document 1] Japanese Patent Application Publication No. 10-329284 DISCLOSURE OF THEINVENTION [Problem to be solved by the invention]
[0006] However, when a laminated sheet having a surface layer of the above-mentioned layer structure laminated on a base layer is overlapped and sewn together for use in a cold storage container product such as a cold storage cover, the aluminum vapor deposition film 52 on the surface layer 51 may partially peel off from the layer 53 containing LDPE and float up, as in the laminated sheet 50 shown in Figure 3. Figure 4 shows a photograph of an actual part where the floating occurred.
[0007] The present invention provides a laminated sheet having a surface layer that prevents this lifting, and a cold storage container using the same. [Means for solving the problem]
[0008] <1> A laminated sheet having a surface layer in which a layer containing low density polyethylene (LDPE) is laminated on a layer containing linear short chain molecular weight polyethylene (LLDPE), and further, an aluminum vapor deposition layer coated with an anchor coat (AC) agent is laminated on the layer containing LDPE, and the AC agent has a dry coating amount of 0.118 g / m 2 The laminate sheet is characterized in that the coating is performed using a gravure roll.
[0009] <2> AC agents are ether-based <1> 2. A method for producing the laminate sheet according to claim 1 .
[0010] <3> The surface layer is laminated on a base layer which is a laminate of a layer containing low density polyethylene (LDPE) and a woven layer made of flat yarns of high density polyethylene (HDPE). <1> or <2> 2. A method for producing the laminate sheet according to claim 1 .
[0011] <4> <1> or <2> The present invention relates to a cold storage container that uses the laminated sheet described above.
[0012] <5> A cooling cover or cooling box <4> 1. A cold storage container according to claim 1.
[0013] In this specification, the term "low density polyethylene" refers to polyethylene as recognized by those skilled in the art, specifically, a polyethylene having a density of 0.910 g / cm3 measured in accordance with Appendix 4-2 of JIS K6922-2. 3 More than 0.930g / cm 3 Less than 100% polyethylene.
[0014] In this specification, the term "surface layer" refers to a layer disposed on the surface side of the laminate sheet and laminated to the base layer in the final step, whereas the term "base layer" refers to a layer other than the surface layer, and may be a single layer or multiple layers. Effect of the Invention
[0015] In the laminate sheet of the present invention, the dry coating amount of the AC agent applied to the aluminum vapor deposition layer is 0.118 g / m 2 Since the coating is carried out using a gravure roll, it is possible to prevent lifting of the aluminum vapor deposition film on the surface layer of the obtained laminate sheet.
[0016] The cold storage container of the present invention uses the laminate sheet of the present invention, and therefore can prevent lifting of the aluminum vapor-deposited film. [Brief description of the drawings]
[0017] [Figure 1] FIG. 1 is a cross-sectional view that illustrates an example of the layer structure of the laminate sheet of the present invention. [Diagram 2] FIG. 2 is a diagram for explaining a sewing method for a sample for evaluating the occurrence of lifting. [Diagram 3] FIG. 3 is a schematic diagram of a conventional laminated sheet in which lifting occurs. [Figure 4] FIG. 4 is a photograph of a portion of a conventional laminated sheet where lifting has occurred. DETAILED DESCRIPTION OF THE PREFERRED EMBODIMENTS
[0018] The laminate sheet of the present invention is used as a heat insulating sheet constituting a cold storage container, and comprises a surface layer and a base layer.
[0019] The surface layer is formed by laminating a layer containing low-density polyethylene (LDPE) on a layer containing linear short-chain polyethylene (LLDPE), and further laminating an aluminum vapor-deposited layer on the layer containing LDPE.
[0020] LLDPE is used to impart flexibility to the sheet and the layer containing it preferably comprises a transparent film.
[0021] There are no particular limitations on the aluminum or deposition method used for the aluminum deposition layer, but it is preferable for the film to be deposited to contain polyethylene terephthalate (PET) since this increases the gloss and improves the appearance.
[0022] An anchor coat (AC) agent is applied to the back side of this aluminum vapor deposition layer to improve adhesion with the layer containing LDPE. The coating amount of this AC agent is 0.118 g / m2 on a dry basis. 2 The dry coating weight must be 0.118 g / m or more. 2 If the amount is less than 100 g / m, the adhesion to the layer containing LDPE is insufficient, and when the laminated sheet is sewn or otherwise processed for use in a cold storage container product after production, the laminated sheet is likely to partially peel off from the layer containing LDPE and float up, i.e., the so-called floating phenomenon occurs. On the other hand, the upper limit of the dry coating amount is 0.20 g / m. 2 The desired effect can be obtained if the amount is within the above-mentioned lower limit, and considering the handling of the AC agent, application of this amount is sufficient.
[0023] There are no particular limitations on the AC agent as long as it is a component that can be used for adhesion of evaporated aluminum, but suitable examples include ether-based and ester-based agents, and of both, ether-based agents are preferred because they are extremely effective in preventing lifting. The AC agent may be subjected to an appropriate aging treatment after application.
[0024] The AC agent is applied to the aluminum vapor deposition layer by a gravure roll. For example, if a flat roll such as a metal roll (Bows roll) is used for application, the AC agent does not blend evenly into the aluminum vapor deposition layer, and lifting is likely to occur during the above-mentioned processing. In other words, the unevenness formed on the surface of the gravure roll can contribute to the AC agent being evenly blended into the layer. Note that there are various types of gravure rolls, such as lattice type, pyramid type, and oblique line type, but since the AC agent has a low viscosity and is metered using a doctor blade and a cell, the lattice type is usually used.
[0025] Here, if the above-mentioned dry coating amount is D, the cell volume of the gravure roll is V, the proportion of the AC agent actually supplied to the layer to be coated, i.e., the transfer rate, is X, the solid content is N, and the specific gravity of the AC agent is 1, then it can be expressed as follows: D = V × X / 100 × N / 100
[0026] Therefore, when V is 6.0 ml, the solid content is 2.8 mass %, the transfer rate is 31.25%, and the specific gravity of the AC agent is 1, the dry application amount can be calculated as follows. D=6.0×0.028×0.3125=0.0525g / m 2
[0027] On the other hand, the base layer may be a single layer or may have two or more layers. However, it is preferable for the base layer to have two or more layers, since this improves flexibility and enables processing to improve strength, such as by inserting a woven layer between layers. Typically, a layer containing low-density polyethylene (LDPE) and a woven layer made of flat yarn of high-density polyethylene (HDPE) are laminated.
[0028] Each layer preferably does not contain any other substances apart from the resin constituting the main component, except for additives necessary or preferable for forming the layer.
[0029] Next, an example of a preferred layer structure of the present invention will be described. Fig. 1 is a cross-sectional view showing the example. The laminated sheet 1 shown in Fig. 1 has a surface layer 2 in which, from the outermost surface, an aluminum-deposited PET (AC-VMPET) layer 3 in which an anchor coating agent is applied to an aluminum-deposited film, an LDPE layer 4 made of an LDPE film, and an LLDPE layer 5 made of an LLDPE film are laminated in this order. The base layer 7 has, from the innermost surface, a first LDPE layer 8, a flat yarn cloth woven layer 9, a second LDPE layer 10, an expanded polyethylene (expanded PE) layer 11, and a third LDPE layer 12 laminated in this order.
[0030] The LLDPE layer 5 constituting the surface layer 2 is a transparent film containing no added colorant, whereas the three LDPE layers constituting the base layer 7 may contain colorants.
[0031] The fabric layer 9 interposed between the first LDPE layer 8 and the second LDPE layer 10 is typically made of high density polyethylene (HDPE, density 0.942 g / cm 3 The sheet is preferably made of flat yarn of at least 10 strands per inch in both directions to improve the strength and durability of the sheet.
[0032] From the viewpoint of improving the strength and durability of the sheet, it is preferable to form the thickness of each LDPE layer slightly thinner toward the inner side, so that, starting from the first LDPE layer 8 on the back side, the first LDPE layer > the second LDPE layer > the third LDPE layer = the LDPE layer of the surface layer. As for the specific thickness range, the first LDPE layer 8 is 30 μm to 50 μm, the second LDPE layer 10, the third LDPE layer 12, and the LDPE layer 4 of the surface layer are all 20 μm to 30 μm, and within that range, it is preferable that the second LDPE layer 10 is about 5 μm thicker.
[0033] The AC-VMPET layer 3, which is the outermost layer, may have a thickness less than half that of each layer made of LDPE. If it is too thick, it may affect the scratch resistance of the sheet.
[0034] The thickness of the LLPDE layer 5 is preferably about four times that of the third LDPE layer 12 and the surface LDPE layer 4, that is, about 80 μm to 200 μm, and the thickness of the foamed PE layer 11 is preferably about 40 times that of the second LDPE layer 10, that is, about 800 μm to 1.2 mm.
[0035] The laminate sheet 1 in FIG. 1 shows a preferred example of the present invention, and is not limited thereto, and may have a different layer structure as appropriate, so long as the surface layer has the layer structure specified in the present invention.
[0036] Furthermore, when producing the laminated sheet of the present invention, the surface layer and the base layer are laminated separately, and then the two are laminated together. As long as a gravure roll is used to apply the AC agent to the aluminum vapor deposition layer of the surface layer, a commonly used laminating machine and laminating method, etc. may be appropriately selected without any particular limitations.
[0037] The laminated sheet of the present invention described above is used for a cold storage container, and can be suitably used for a cold storage cover or a cold storage box, as described above. In addition, it can be suitably used for various applications requiring heat insulation, such as a light-shielding curtain for an automobile.
[0038] The cold storage container of the present invention may have any configuration, and is not particularly limited, so long as it uses the laminate sheet of the present invention in a commonly available form. EXAMPLES
[0039] Examples of the present invention will be described below, but the present invention is not limited to these examples.
[0040] Example 1 [Making laminated sheets] The surface layer and the base layer were laminated separately by a conventional method, and then the two were laminated together to produce a laminated sheet of the present invention (Example) having the layer structure shown in Figure 1. In this case, an ester-based AC agent RL-1 (manufactured by Toyo Ink Co., Ltd.) was used as the AC agent, and the AC-VMPET layer 3 was formed by applying it to the aluminum vapor deposition film of the surface layer using a gravure roll. The gravure roll has a grid shape, a line count of 220, a depth of 35 μm, and a width of 1 m. 2 The cell volume per unit volume was 10 ml. The thickness of each layer of the laminate sheet and the amount of additives are as follows. Additives other than those listed are not included, or even if they are included, they are in such small amounts that they do not affect the physical properties. (1) Surface layer (from the outermost surface) (a) AC-VMPET layer, thickness 12 μm (b) Surface LDPE layer: 20 μm thick, dry coating amount 0.118 g / m 2 (Transfer rate 32%, solid content 3.70% by mass) (c) LLDPE layer, thickness 80 μm (2) Base layer (from the back side) (a) First LDPE layer, 30 μm thick (b) Fabric layer: HDPE cloth, 10×10 thread count, 950 denier (c) Second LDPE layer, 25 μm thick (d) PE foam layer, thickness 1mm (e) Third LDPE layer, 20 μm thick
[0041] [Evaluation of the presence or absence of floating] After the obtained laminated sheet was subjected to aging treatment, two laminated sheets (cooled raw sheets) were overlapped and diagonally stitched at intervals of about 50 mm as shown in FIG. 2 to obtain a sample of Example 1. In the surface layers of three of these samples (n=3), the AC-VMPET layer 3 was visually observed for lifting from the LDPE layer 4, that is, the location of lifting, and a relative sensory evaluation was performed on a five-level scale from 0 to 4. Specifically, when no lifting was observed, it was evaluated as 0, and the relatively more frequently the lifting was observed, the larger the evaluation number was, such as 1, 2, 3, ..., and when it was judged that the lifting occurred most frequently and peeling was observed frequently, it was evaluated as 4. The results are shown in Table 1.
[0042] Comparative Example 1 In Example 1, the dry coating amount of the AC agent was 0.038 g / m 2 Except for changing the solid content concentration to 1.20% by mass, a sample was sewn and evaluated in the same manner as in Example 1. The results are shown in Table 1.
[0043] Example 2 In Example 1, the dry coating amount of the AC agent was 0.192 g / m 2 Except for changing the solid content concentration to 6.00% by mass, a sample was sewn and evaluated in the same manner as in Example 1. The results are shown in Table 1.
[0044] Example 3 A sample was sewn and evaluated in the same manner as in Example 1, except that the AC agent in Example 1 was changed to an ether-based AC agent LX470EL (manufactured by DIC Graphics). The results are shown in Table 1.
[0045] Example 4 In Example 3, the dry coating amount of the AC agent was 0.192 g / m 2 Except for changing the solid content concentration to 6.00% by mass, a sample was sewn and evaluated in the same manner as in Example 3. The results are shown in Table 1.
[0046] Example 5 In Example 3, the gravure roll for applying the AC agent had a lattice shape with a line count of 250, a depth of 17 μm, and a width of 1 m.2 The cell volume per cell was changed to 6.5 ml, and the dry coating amount was changed to 0.184 g / m 2 Except for changing the solid content concentration to 9.00% by mass, a sample was sewn and evaluated in the same manner as in Example 3. The results are shown in Table 1.
[0047] Comparative Example 2 In Example 1, the AC agent was applied to the aluminum vapor-deposited film using a metal roll (also called a "Bows roll") with no irregularities on its surface instead of the gravure roll, and the solid content concentration of the AC agent was 2.40 mass%, i.e., the application amount was 2 / 3. Except for this, samples were sewn and evaluated in the same manner as in Example 1. The results are shown in Table 1.
[0048] Comparative Example 3 A sample was sewn and evaluated in the same manner as in Example 2, except that the AC agent was applied to the aluminum vapor-deposited film using a Bowes roll instead of the gravure roll in Example 1. The results are shown in Table 1.
[0049] Comparative Example 4 A sample was sewn and evaluated in the same manner as in Example 3, except that the AC agent was applied to the aluminum vapor-deposited film using a Bowes roll instead of the gravure roll in Example 2. The results are shown in Table 1.
[0050] Comparative Example 5 A sample was sewn and evaluated in the same manner as in Example 5, except that the AC agent was applied to the aluminum vapor-deposited film using a Bowes roll instead of the gravure roll in Example 4. The results are shown in Table 1.
[0051] [Table 1]
[0052] From the results in Table 1, the dry coating amount was 0.118 g / m 2In the samples of Examples 1 to 5 in which the above AC agents were applied to the aluminum vapor-deposited film using a gravure roll, no lifting of the aluminum vapor-deposited film was observed at all or only a very small amount occurred, and lifting of the aluminum vapor-deposited film from the LDPE layer was prevented.
[0053] On the other hand, the dry coating weight is 0.118 g / m 2 In the samples of Comparative Examples 1 to 5 in which the AC agent was applied using a Bowes roll having a surface with less unevenness or no unevenness, the occurrence of lifting was noticeable, and in some cases it occurred frequently.
[0054] From this, the AC agent was set at 0.118 g / m 2 It is presumed that by applying the above dry coating amount using a gravure roll, the AC agent is distributed evenly and in sufficient quantity on the aluminum vapor-deposited film, improving adhesion to the surface LDPE layer and preventing peeling, or lifting, of the aluminum vapor-deposited film.
[0055] In addition, it was found that the use of an ether-based AC agent was preferable because it completely prevented lifting. The reason for this is not entirely clear, but it is thought to be due to the fact that ether-based AC agents have better flexibility on the substrate to which they are applied than ester-based AC agents. [Industrial Applicability]
[0056] The present invention can be applied to applications requiring thermal insulation, such as cold storage containers such as cold storage covers and cold storage boxes. [Explanation of symbols]
[0057] 1 Laminated sheet 2 Surface layer 3 AC-VMPET layer 4 LDPE layers 5 LLDPE layers 7 Base material layer 8 First LDPE layer 9 woven layers 10 Second LDPE layer 11 PE foam layer 12 3rd LDPE layer
Claims
1. A laminated sheet having a surface layer in which a layer containing low density polyethylene (LDPE) is laminated on a layer containing linear short chain polyethylene (LLDPE), and further, an aluminum vapor deposition layer coated with an anchor coat (AC) agent is laminated on the layer containing LDPE, The dry coating amount of the AC agent was 0.118 g / m 2 The laminate sheet is characterized in that the coating is performed using a gravure roll.
2. 2. The method for producing a laminate sheet according to claim 1, wherein the AC agent is an ether type.
3. 3. The laminate sheet according to claim 1 or 2, wherein the surface layer is laminated to a base layer comprising a layer containing low density polyethylene (LDPE) and a woven layer made of flat yarns of high density polyethylene (HDPE).
4. A cold storage container comprising the laminated sheet according to claim 1 or 2.
5. 5. The cold storage container according to claim 4, which is a cold storage cover or a cold storage box.
Citation Information
Patent Citations
JP1988053731U
Heat insulating laminated sheet and use thereof
JP1998329284A
Cold-insulation bag
JP2002173181A
Laminated sheet and cold insulation container
JP2019181771A
Heat insulation sheet and heat insulation box
JP2020142401A
Cited By
Profiled strip with a water drainage element
US12570361B2